Application of online to offline teaching mode in the training of non-anesthesiology residents in the department of anesthesiology: a randomized, controlled trial - Zhao, Yuan-yuan; Zhang, Ting-ting; Li, Ling-hui; Liu, Qian; Peng, Li-juan; Wang, Qi; Wang, Wei; Yu, Wan-you (Frontiers in Medicine, 2024)
Objective To explore the effect of applying the online to offline teaching mode in the training of non-anesthesiology residents in department of anesthesiology. Trial design The randomized controlled trial was performed on non-anesthesiology residents from Affiliated Jiangning Hospital of Nanjing Medical University. Methods All selected residents were randomly divided into the traditional teaching group (Group T) and the online to offline teaching group (Group O) by the random number table method. Traditional teaching mode was used in Group T, while the online to offline teaching mode was used in Group O. The training period lasted for two months. At the end of the training, theoretical and clinical skills were assessed for all residents, and students’ satisfaction scores on teaching were investigated from the aspects of teaching mode, stimulating learning interest, improving learning process and teaching satisfaction. The teaching efficiency was compared and analyzed in the two groups. Results In total, 39 cases in Group O and 38 cases in Group T were included in the statistical analysis. Compared with Group T, theory test scores, clinical skills test scores, and overall scores improved significantly in Group O (82.2 ± 8.1 vs. 91.3 ± 7.6; 85.1 ± 4.7 vs. 93.3 ± 5.4 and 83.4 ± 6.4 vs. 92.1 ± 6.7, respectively, p < 0.01). Compared with Group T, scores on teaching mode, stimulating learning interest, improving learning process and teaching satisfaction were higher in Group O (81.1 ± 6.9 vs. 93.7 ± 5.2; 83.6 ± 5.8 vs. 91.6 ± 6.4; 82.4 ± 5.3 vs. 90.9 ± 4.8 and 82.1 ± 5.9 vs. 92.1 ± 5.5, respectively, p < 0.01). Conclusion The online to offline teaching mode can improve the level of professional theory and clinical skill operation, and teaching satisfaction of the non-anesthesiology residents in department of anesthesiology, thus improving the teaching effectiveness.